Attribution of Source Specific 370 nm UV Light Absorption from Dust, Brown Carbon, and Black Carbon at Two Locations in the San Joaquin Valley - Michael R. Olson; Alexandra Lai; Matthew Skiles; James J. Schauer (Aerosol and Air Quality Research)
Abstract Yearlong, one-in-three-day, source apportionment results were applied to literature values of source specific BrC, BC, and dust mass absorption cross-sections (MAC) to estimate the source contribution to 370 nm near-UV light absorption at Fresno and Bakersfield, San Joquin Valley (SJV), California. The reconstructed light absorption agreed well (r2 of 0.94 Fresno and 0.90 Bakersfield) with co-located AE33 aethalometer measurements. Near-UV absorption was attributed to total mobile, vegetative detritus, wood combustion, meat cooking, SOA, and dust sources. Winter BrC absorption was dominated by wood combustion, accounting for 67% (Fresno) and 53% (Bakersfield) of light absorption at the sites. In summer, wood combustion only accounted for approximately 7% of the near-UV absorption in the SJV. Summer absorption, while significantly lower than winter values, was dominated by SOA and vehicle emissions. In Fresno, summer absorption was comprised of 35% SOA, 39% vehicle BC and 15% vehicle BrC. Bakersfield’s summer absorption was 27% SOA, 44% vehicle BC, and 14% vehicle BrC. Total BrC absorption correlated well with OC concentrations, when segregated out by season, while the total BrC absorption was highly variable when compared to WSOC concentrations. The results indicate using source specific MAC values is an effective way to model near-UV light absorption associated with BrC sources and mitigation approaches that prioritize wood combustion in winter and vehicle emissions in summer would have the greatest effect in reducing near-UV light absorption in the SJV.